Innate and Adaptive Immune Genes Associated with MERS-CoV Infection in Dromedaries - Lado, Sara; Elbers, Jean P; Plasil, Martin; Loney, Tom; Weidinger, Pia; Camp, Jeremy V; Kolodziejek, Jolanta; Futas, Jan; Kannan, Dafalla A; Orozco-terWengel, Pablo; Horin, Petr; Nowotny, Norbert; et al. (Cells, 2021)
The recent SARS-CoV-2 pandemic has refocused attention to the betacoronaviruses, only eight years after the emergence of another zoonotic betacoronavirus, the Middle East respiratory syndrome coronavirus (MERS-CoV). While the wild source of SARS-CoV-2 may be disputed, for MERS-CoV, dromedaries are considered as source of zoonotic human infections. Testing 100 immune-response genes in 121 dromedaries from United Arab Emirates (UAE) for potential association with present MERS-CoV infection, we identified candidate genes with important functions in the adaptive, MHC-class I (HLA-A-24-like) and II (HLA-DPB1-like), and innate immune response (PTPN4, MAGOHB), and in cilia coating the respiratory tract (DNAH7). Some of these genes previously have been associated with viral replication in SARS-CoV-1/-2 in humans, others have an important role in the movement of bronchial cilia. These results suggest similar host genetic pathways associated with these betacoronaviruses, although further work is required to better understand the MERS-CoV disease dynamics in both dromedaries and humans.
Keywords: Spojené arabské emiráty; zoonosis; Zoonoses; přirozená imunita; bronchy; Male; immune response genes; Genetic Predisposition to Disease; protilátky virové; replikace viru; zdroje nemoci; Old World camels; objevující se infekční nemoci; koronavirové infekce; zoonózy; in-solution hybridization capture; mužské pohlaví; SARS-CoV-2; Immunity, Innate; cilie; interakce mikroorganismu a hostitele; Host Microbial Interactions; United Arab Emirates; Animals; lidé; ženské pohlaví; Virus Replication; Communicable Diseases, Emerging; koronavirus MERS; Humans; zvířata; adaptivní imunita; Disease Reservoirs; velbloudi; Middle East Respiratory Syndrome Coronavirus; Adaptive Immunity; Antibodies, Viral; Cilia; respirační sliznice; Respiratory Mucosa; Bronchi; Coronavirus Infections; Female; coronavirus; genetická predispozice k nemoci; Camelus; COVID-19